2020
DOI: 10.1111/aor.13684
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of occlusion methods for artificial sphincters

Abstract: An artificial sphincter is a device that replaces the function of the biological sphincter by occluding the relative biological lumen. The investigation of occlusion methods for artificial sphincters is crucial for a reliable and effective design of such devices. The compression induced onto the tissue by a certain pressure depends on the biomechanical and physiological features of the lumen and on the specific occlusion method. A numerical model and an experimental evaluation are presented here to assess the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…The compression induced onto the tissue by a certain pressure depends on the biomechanical and physiological features of the tissues itself and the specific occlusion method. 3 It is almost impossible to measure the deformation and hightension (stress) levels acting on the biological tissues due to the AS permanence on the body and, especially, during the occlusive action. To overcome the complications and the failures of the existing devices, it is desirable a more rational approach based on the methods of bioengineering.…”
Section: For Assmentioning
confidence: 99%
See 3 more Smart Citations
“…The compression induced onto the tissue by a certain pressure depends on the biomechanical and physiological features of the tissues itself and the specific occlusion method. 3 It is almost impossible to measure the deformation and hightension (stress) levels acting on the biological tissues due to the AS permanence on the body and, especially, during the occlusive action. To overcome the complications and the failures of the existing devices, it is desirable a more rational approach based on the methods of bioengineering.…”
Section: For Assmentioning
confidence: 99%
“…To overcome the complications and the failures of the existing devices, it is desirable a more rational approach based on the methods of bioengineering. Computational studies treating the tissue-device interaction and the occlusion methods have been proposed in order to develop new and optimized ASs able to simulate natural sphincters, 3,23,24 minimize tissue damage and ischemia, and improve AS effectiveness and reliability. Preclinical testing of medical devices designed for humans must be evaluated first by a series of in vitro and in vivo tests.…”
Section: For Assmentioning
confidence: 99%
See 2 more Smart Citations
“…
Fecal incontinence (FI) is a common clinical symptom, which refers to the inability to control defecation and cause the leakage of intestinal contents. 1 The incidence of FI in adults is 7%-15% and the older the age, the higher the incidence. 2 Studies have shown that the incidence of elderly people over 65 years old is as high as 18.30%.
…”
mentioning
confidence: 99%